William Grant Still and the Balance of Popular Vs. Classical: Pace & Handy, Black Swan, and Shuffle Along - (:unkn) unknown (My University, 2014)
Although known for his classical compositions, the African American composer William Grant Still worked in the popular music market at Pace & Handy Music Publishing, Black Swan Records, and as an orchestrator and pit musician for the black musical, Shuffle Along. These are all early experiences that must be considered when discussing his later success in art and popular music and that can offer valuable insight for scholars. In order to understand these employment experiences, this thesis places Still in the cultural context of early-1920s New York. By examining the ideology of racial uplift and the African American entertainment scene in the 19th and early 20th centuries, a better understanding of Still's experience is gained. The experiences he had in early 1920s New York did not encompass his popular music output alone, but a much wider and important experience of learning, as a young black man, about how to function in a society where racial stereotypes directly played a role in how African Americans were viewed--not only within their own race but also within the social structure of the wider American culture.
Keywords: Black Swan; Minstrelsy; Pace & Handy; Publishing; Shuffle Along; William Grant Still